University professor competencies: Development and validation of a selfassessment questionnaire [Competencias del profesor universitario: Elaboración y validación de un cuestionario de autoevaluación] - Aguilar Feijoo, R. (2015)
It is essential to know the core competences of a university teacher so as to meet their pedagogical training needs. With this objective in mind, we aimed to develop a self-evaluation quiz (using 20 competences and 114 indicators), which covered the four main functions of a university teacher. This article describes the evaluation and validation process of this test. The validation of the content was based on the judgment of experts, the usage of Cronbach's alpha coefficient, (obtaining values between 0.88 and 0.99), a pilot project using values 0.92-0.97, the final application of the testing instrument, a two-halves test (for testing internal consistency), as well as moderate -strong associations. The results show that the applied instrument can be successfully used- based on its high level of reliability- to diagnose both generic and specific competences.